Interação albendazol–praziquantel em voluntários sadios : disposição cinética, metabolismo enantiosseletividade - Lima, Renata Monteiro (2008)
The praziquantel (PZQ), a chiral drug available as racemic, and the albendazole (ABZ), a drug biotransformed into active metabolic chiral suphoxide of abendazol (ASOX), have been used in the treatment of human neurocysticercosis. The study covers the examination / search of the kinetic disposition, the metabolism, and the enantioselectiveness in the ABZ-PZQ association in healthy volunteers. The crossed and random study was developed in three phases (n=9), in which some volunteers started by PHASE 1 (400 mg of ABZ), others by PHASE 2 (1500mg of PZQ), and others by PHASE 3 (400 mg of ABZ + 1500mg of PZQ). The period of washout was of a minimum of 15 days (PHASE 1 followed by PHASE 2 and PHASE 1 followed by PHASE 3) or of 7 days (PHASE 2 followed by one of the other Phases). The serial blood samples were collected in a period of 0-48 hours. The ABZ metabolics were analised by HPLC with detection by fluorescence and the PZQ enantiomers and the trans-4-hydroxypraziquantel (4-OHPZQ) were analised by LC-MS-MS. The pharmacokinetic patterns were determined with the help of the WinNonlin program. The test of Wilcoxon (p≤0.05) was used to evaluate the enantiomer ratios of plasma concentrations of ASOX, PZQ and 4-OHPZQ. The data are shown as medians. The kinetic disposition of the PZQ, 4-OHPZQ and ASOX is enantioselective in the monotherapy situation; the ratios of AUC are of 2.97 to (+)-(S)-PZQ / (-)-(R)-PZQ, 0.78 to (+)-(S)-4-OHPZQ / (-)-(R)-4-OHPZQ, and 7.08 to (+)-ASOX / (-)-PZQ. The administration of the PZQ results in the increase of the plasma concentrations of the (+)-ASOX in 264% (AUC 980.42 vs 2591.80ng.h./ml), of the (-)-ASOX in 358% (139.59 vs 500.28ng.h./ml), and of the sulphona of albendazole in 187% (170.85 vs 319.50ng.h./ml), suggesting the PZQ as an inhibiting factor of the intestinal Pgp. The administration of the ABZ does not change/ alter the kinetic disposition of the (+)-(S)-PZQ, and of the metabolic (-)-(R)-4-OHPZQ and (+)-(S)-4-OHPZQ, but it results in the increase of the plasma concentrations of the (-)-(R)-PZQ in 64.77% (AUC 518.02 vs 853.57ng.h./ml ), suggesting enantioselective inhibition of the metabolism of the ASOX. The data allow us to suggest the possibility of increase of therapeutic efficacy in the ABZ-PZQ interaction; although, other studies are necessary to evaluate the safety of the interaction.